Numerical study on scroll vortex intake with partially or fully sealed cover of vortex chamber - Wang, Yiran (2024)
When installed in deep tunnel systems, the cover of the vortex dropshaft may be partially or fully sealed. With air exchange restricted through the cover, the air supply to the dropshaft through the inflow channel might not be adequate. Hence, further investigation is required to examine the effect of the restricted air passage through the cover on the flow regimes and hydraulic performance of the scroll vortex dropshaft. This study aims to quantify the head-discharge relationship, air-water distribution, and minimum air core size with different cover opening conditions. The 3D model of a fully open scroll vortex dropshaft is constructed, and numerical simulations are carried out and validated using experiment data. The results show that the effect is generally small when the ratio of the opening and dropshaft area is larger than 1%. When the cover is fully sealed, the minimum air core size reduces by ~5% of the dropshaft area which can have a serious implication to the design of the scroll vortex dropshaft. The present study provides a practical evaluation of the effect of the opening condition in the cover of the vortex chamber on the performance of scroll vortex dropshafts for underground water drainage systems.